Peran Pemberdayaan Pam Swakarsa Satpam Oleh Unit Binkamsa Dalam Mencegah Tindak Pidana Pencurian Dengan Pemberatan - SYAHRIR, MUHAMMAD SYAHRIR HUSAIN (Police Studies Review, 2020)
This study aims to look at how the empowering role of Pam Swakarsa by Binkamsa Unit in preventing the crime of theft by weighting in Majalengka Police area. There are several factors that cause nozzle case occurs, the living environment, work environment, economic factors and others. The research on the role of security guard by the Binkamsa Unit is intended to improve the performance of the Binkamsa Unit so that it can provide maximum guidance to the Security Guard. Therefore, a study was conducted to find out the general picture of Curat criminal acts in Majalengka, the implementation of security guards by the Binkamsa Unit, and the factors that influenced the process of empowering security guards by the Binkamsa Unit. This research was discussed using concepts and theories, namely using the concept of criminal offenses Article 363 of the Criminal Code, the concept of the Binkamsa Sop Unit, the concept of roles, the concept of empowerment, management theory and the theory of management elements (6M). The approach used by researchers is a qualitative approach, using descriptive analysis methods and data collection techniques through observation, interviews, and document review. This study was discussed using concepts and theories, namely using the concept of Curat criminal acts article 363 of the Criminal Code, the concept of the Binkamsa Sop Unit, the concept of roles, the concept of empowerment, management theory and elements of research. in the past four years. The role of the security guards carried out by the Majalengka District Police Binkamsa Unit has not been maximized due to several obstacles. These constraints include the lack of personnel, the quality of human resources has not been evenly distributed, there is no budget that supports the empowerment process, lack of planning and administrative arrangements that are not orderly and still lack of coordination from the security service provider or security guard service users. From the findings of the study, the authors recommend the Majalengka District Police to increase the number of personnel and the provision of Dikmas Binmas personnel, make good planning so that each activity can be carried out, realize the amount of the existing budget, build good relations and communication with the security guards and security service users. in the Majalengka region. ur management (6M). The approach used by researchers is a qualitative approach, using descriptive analysis methods and data collection techniques through observation, interviews, and document review.